Relationship Between QRS Duration on ECG and LV Systolic Function by Echocardiography in Patients with STEMI - Hossain, Md Billal; Chowdhury, Msi Tipu; Islam, Md Zahidul; Debnath, Rakhal Chandra; Banerjee, Sajal Krishna; Bari, M Saiful (University Heart Journal, 2019)
Background: Acute STEMI patients constitute a large proportion of admissions in coronary care unit and their management and prognostic implification is of immense importance. Prolonged QRS duration on electrocardiogram (ECG) has been associated with cardiac structural and functional abnormalitiesVery few studies were performed correlating QRS duration and LV systolic function in acute STEMI patients in our country. This study assessed whether QRS duration on ECG is correlated with LV systolic function measured in patients with acute STEMI. Aim of the Study: The aim of the study is to evaluate the relationship between QRS duration on ECG with left ventricular systolic function by echocardiography in patients with acute ST elevation myocardial infarction. Methods: A cross sectional observational study was conducted in the department of Cardiology in Mymensingh Medical College Hospital from November, 2016 to February, 2018 among purposively selected 235 patients with STEMI following inclusion & exclusion criteria. After detailed history, physical examination and investigations the selected patients underwent transthoracic Echocardiography to asses left ventricular systolic function applying Teichholz method. Results: Mean age of the patients 51.84±11.74 years. 135(57.45%) patients had acute anterior MI, while 98(41.70%) had Inferior MI and only 2(0.85%) had lateral MI. Mean QRS duration was 93.3 ±10.18 ms, with maximum value 125ms and minimum value 66ms. Mean left ventricular ejection fraction was 49.71%±9.87%, with maximum value 74% and minimum value 23%. QRS duration and left ventricular ejection fraction were moderate negative correlation with r= -0.611, <P = 0.001. Conclusion: The study concluded that QRS duration is negatively correlated with Left ventricular systolic function in patients with acute ST elevation myocardial infarction. University Heart Journal Vol. 15, No. 2, Jul 2019; 54-59